The strategy of professional forecasting☆ - OTTAVIANI, M; SORENSEN, P (Journal of Financial Economics, 2006)
We develop and compare two theories of professional forecasters’ strategic behavior. The first theory, reputational cheap talk, posits that forecasters endeavor to convince the market that they are well informed. The market evaluates their forecasting talent on the basis of the forecasts and the realized state. If the market expects forecasters to report their posterior expectations honestly, then forecasts are shaded toward the prior mean. With correct market expectations, equilibrium forecasts are imprecise but not shaded. The second theory posits that forecasters compete in a forecasting contest with pre-specified rules. In a winner-take-all contest, equilibrium forecasts are excessively differentiated.